Astragalus garinensis (Galegeae, Fabaceae), a new species in the west of Iran - Dehshiri, Mohammad Mehdi; Maassoumi, Ali Asghar (Phytotaxa, 2026)
Astragalus garinensis Maassoumi & Dehshiri (Galegeae, Fabaceae), is described and illustrated as a new endemic species in the west of Iran. It is native to Garin mountain and Oshtoran Kouh. It grows only on rocky mountain slopes at elev. 3000–3200 m, and belongs to the section Incani due to its medifixed hairs, free stipules, bibracteolate flowers, and imparipinnate leaves. It is similar, and probably most closely related to A. cellatus Maassoumi. The diagnostic characteristics, as well as a full description, taxonomic comments, conservation status and figures of the species are discussed and compared with A. cellatus.